EXPLORING THE HUMAN CIRCULATORY SYSTEM THROUGH SYSTEM DYNAMICS: A MODEL-BASED APPROACH - IAPĂSCURTĂ, Victor (Journal of Engineering Science (Chişinău))
System dynamics is a robust methodology for understanding the behavior of complex systems over time. By employing feedback loops, stocks, flows, and time delays, this approach provides a comprehensive framework for simulating and analyzing dynamic systems. The application of system dynamics to the human circulatory system presents numerous possibilities, benefits, and practical applications that can significantly enhance our understanding and management of cardiovascular health. This article details experimental results from modeling myocardial infarction conditions using a six-compartment model developed in the NetLogo integrated development environment, incorporating BehaviorSpace for extensive simulations. For result analysis, specialized packages in R, Python, and Wolfram Mathematica were utilized to ensure rigorous data interpretation. The results demonstrate promising fidelity when compared to existing literature and real-time patient data, indicating the model's potential for clinical applications. By illustrating the interactions within the circulatory system, this research not only contributes to theoretical knowledge but also offers practical insights into disease management and intervention strategies, paving the way for improved cardiovascular health outcomes.